2018
DOI: 10.1007/s10822-018-0122-1
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel wee1 inhibitors via structure-based virtual screening and biological evaluation

Abstract: Wee1 plays a critical role in the arrest of G2/M cell cycle for DNA repair before entering mitosis. Many cancer cells have been identified as overexpression of Wee1. In this research, pharmacophore modeling, molecular docking and molecular dynamics simulation approaches were constructed to identify novel potential Wee1 inhibitors. A compound 8 was found to have a novel skeleton against Wee1 with an IC value of 22.32 µM and a K value of 13.11 µM. Kinetic assays were employed to evaluate the compound 8 as a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…137 5) were identified. 141 In the same year, Hu et al screened the ZINC database via ligand-based pharmacophore modeling and identified eight potential ligands with new scaffolds, which were further subjected to QSAR, ADMET, and binding free energy studies followed by molecular dynamics (MD) simulations and ultimately proposed 3 (Figure 5) as a potent WEE1i. 142 Furthermore, vanillates (4) (Figure 5) have also exhibited micromolar WEE1 inhibition and were initially treated as an important class of WEE1i.…”
Section: Synthesis Of Pyrazolopyrimidine Analoguesmentioning
confidence: 99%
See 3 more Smart Citations
“…137 5) were identified. 141 In the same year, Hu et al screened the ZINC database via ligand-based pharmacophore modeling and identified eight potential ligands with new scaffolds, which were further subjected to QSAR, ADMET, and binding free energy studies followed by molecular dynamics (MD) simulations and ultimately proposed 3 (Figure 5) as a potent WEE1i. 142 Furthermore, vanillates (4) (Figure 5) have also exhibited micromolar WEE1 inhibition and were initially treated as an important class of WEE1i.…”
Section: Synthesis Of Pyrazolopyrimidine Analoguesmentioning
confidence: 99%
“…159 In contrast, compound libraries containing glutarimide-structural frag-ments were synthesized and screened for compounds promoting the ubiquitination of WEE1. WX106 (141), a CRBN competitive binder, induced the desired proteasomedependent degradation of WEE1 and is effective against 18 cell lines tested. 161 The toxicity of AZD1775 is a result of off-target and on-target inhibition, but the corresponding PROTACs offer ample selectivity and probably no off-target toxicity and tolerable on-target toxicity.…”
Section: Degraders Of Wee1 Kinasementioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the recent advances in the development of molecular modeling techniques for the search of biologically active compounds cannot be overlooked. The literature describes cases of successful application of pharmacophore screening [28,29], molecular docking, and molecular dynamics [30][31][32] to identify new chemical structures with anti-kinase activity. In addition, the improvements in technical and theoretical background of machine learning algorithms have made it possible to adapt them, inter alia, for the modeling of protein-ligand interactions [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%